2013
DOI: 10.1016/s1001-0742(12)60319-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community structure and function responses to successive planting of Eucalyptus

Abstract: Many studies have shown soil degradation after the conversion of native forests to exotic Eucalyptus plantations. However, few studies have investigated the long-term impacts of short-rotation forestry practices on soil microorganisms. The impacts of Eucalyptus successive rotations on soil microbial communities were evaluated by comparing phospholipid fatty acid (PLFA) abundances, compositions, and enzyme activities of native Pinus massoniana plantations and adjacent 1st, 2nd, 3rd, 4th generation Eucalyptus pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 53 publications
(54 reference statements)
3
21
0
1
Order By: Relevance
“…Many factors in the forest ecosystem can affect microbial communities (Janssens et al, ). Significant shifts in the microbial communities in response to the successive planting of Eucalyptus have also been found in previous work (Chen et al, ; Wu et al, ). Nevertheless, the methods used in these studies do not accurately determine which bacteria have undergone significant changes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Many factors in the forest ecosystem can affect microbial communities (Janssens et al, ). Significant shifts in the microbial communities in response to the successive planting of Eucalyptus have also been found in previous work (Chen et al, ; Wu et al, ). Nevertheless, the methods used in these studies do not accurately determine which bacteria have undergone significant changes.…”
Section: Discussionsupporting
confidence: 83%
“…These values may be correlated with the high organic matter content in the stand. We found that the high acid phosphatase levels observed in high phosphorus soils may be due to phosphatase activating the phosphorus, which is vital for improving soil phosphorus availability in this area (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater pollution has become much heavier over the past few decades and more than 60% of rivers have become polluted in the Haihe Basin . There is a clear qualitative relationship between N surplus and nitrate concentrations in the groundwater in a given crop-growing area, meaning that massive N accumulations in fields are likely to increase the risk of groundwater nitrate contamination (Zhao et al, 2009b;Hou et al, 2012;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…, Chen et al. ). In this study, we found a species‐specific partitioning of microbial communities in response to drought treatments and phosphorus addition (Appendix : Table S2; Figs.…”
Section: Discussionmentioning
confidence: 99%
“…, Chen et al. ). However, little is known about the response of soil microbiota, including protozoa, microbes, and associated enzyme activities, to the specific identity of aboveground tree species (nitrogen and non‐nitrogen‐fixing) or even the absence of vegetation, particularly in the presence or absence of other ecosystem‐limiting factors (drought and P addition).…”
Section: Introductionmentioning
confidence: 99%